The Rhythm of Strategy A Corporate Biography of the Salim Group of Indonesia - Dieleman, Marleen (ICAS Publications Series, 2007)
This book provides a well-documented analysis of the strategy of the Salim Group, one of the largest family conglomerates in Southeast Asia. Using a multitude of sources, including interviews with the Salim family and Salim Group managers, the author provides a comprehensive corporate biography of this fascinating family firm. The Rhythm of Strategy: A Corporate Biography of the Salim Group of Indonesia criticises existing theories on ethnic Chinese firms and instead provides a more nuanced view of the evolution of a small migrant trading business into the largest family business group in Southeast Asia. It argues that the strategy of this group oscillated irregularly between a business model built on connections and a professional business model adapted to markets. Due to its size and closeness to the Suharto regime, the Salim Group has played an important role in shaping Indonesia's economy. This title is available in the OAPEN Library - http://www.oapen.org.